Long-term Results of in Situ Pinning Treatment of Femoral Head Slippage Patients - Kayahan Karaytuğ; Gökhan Polat; Turgut Akgül; Ali Asma; Cengiz Şen; Mehmet Aşık (İstanbul Medical Journal, 2018)

(untitled)
Introduction: Slipped capital femoral epiphysis (SCFE) is a disease that occurs as a result of the posterior and inferior displacement of the femur head. SCFE is the most common hip pathology in adolescence. It is classified as stable and unstable SCFE according to the loadability of the affected leg. The widely accepted method for stable SCFE treatment is in situ pinning. In situ pinning is an effective method for relieving pain in the early period and preventing the progression of slippage. On the other hand, because of the non-anatomic reduction of physis, it is expected in middle and long-term osteoarthritis. Our aim in this study is to report the long-term functional outcomes of patients with SCFE who were treated with in situ fixation at a trauma center.Methods: This study was designed as a retrospective collection of data at a tertiary trauma center, and descriptive research based on prospective assessment and observation. Patients who were treated with closed-loop in situ pinning were evaluated retrospectively for acute, subacute, and chronic slip intensity according to the Southwick classification as mild, moderate, severe, and load-failing. Patient satisfaction surveys (SF-12, WOMAC, HHS, and HOS) were used to evaluate postoperative clinical and functional outcomes.Results: Overall, 33 patients were included in the study, and 38 hips (28 unilateral, 5 bilateral) were treated surgically. In total, 11 patients (33.3%) had no complaint. In 11 patients (33.3%), the main complaint was limping. The main complaint of 7 patients (21.2%) was restricted movement, and 4 patients (12.1%) were found to have underlying pain. The mean functional results of the patients after the first surgical treatment were HHS, 82.6; HOS, 87.2; WOMAC, 82.8; SF-12 PCS, 43.8. The SF-12 MCS was found to be 48.2.Conclusion: In this study, satisfactory results were obtained early in the in situ pinning method, and it was not enough to prevent osteoarthritis but other morbid complications in the long term.